The Impact of Information Quality and Usability on Intention to Use Student Information System - Atta, Mohammed Thamir; Awanis, Romli (American Scientific Publishers, 2018)
Educational institutions become more dependent on information systems because of the essential functions that can benefit from these systems. The aim of this research is to evaluate and update the success model of DeLone and McLean based on their theory of information system in order to be implemented in academic environment. This study introduced usability, information quality, the intention to use SIS, and user’s satisfaction in the domain of information systems. The findings form this study shows that information quality of content provided by SIS, the usability of system interface, and the intention to use student information system, all these three variables affect user's satisfaction in higher education institutions. The study recommends to focus on quality measures of content and usability of system which in turn increase the intention of students to use student information system and enhance their satisfaction about the system.